Perancangan Visual Feed Instagram Lazdau Guna Menciptakan Desain Yang Menarik (International Forum of Researchers and Lecturers, 2025)
This rapid era of civilization has greatly influenced human life. As time goes by, technology and design keep up with the times. Social media is a form of development of the times and plays a big role in modern society. Nowadays, the controlling media is the internet, where social media refers to platforms on the internet that allow users to share content, interact and connect with other people online. Of course, this requires design to provide a visual experience for the public. Design principles used to create online communication platforms. The main focus is on a comfortable user experience so that it can attract the attention of Instagram users.